Lost in Transition: The Costs and Consequences of Sectoral Labour Adjustment - Stephen Tapp (Queen's University, Department of Economics, 2007)
This paper demonstrates that factors which impede labour market adjustments can have first-order impacts on aggregate output and social welfare. While several studies find that individual workers can face large and persistent sectoral reallocation costs, this paper shows that these costs are important at the aggregate level. I use a search and matching model to isolate and quantify two factors that contribute to the costly and time-consuming adjustment process: search frictions and an inability to transfer match-specific skills to new jobs. I apply the model to examine Canada's sectoral labour adjustment after a global increase in commodity prices and associated exchange rate appreciation. These developments reorganized production to the resource sector and away from manufacturing. The model quantitatively captures both the sectoral employment and wage effects and the response of unemployment to changes in unemployment benefits. The model estimates that the costs of adjustment are economically important, accounting for up to three percent of output during the transition. These costs arise mainly in the first three years after the shock and are due largely to non-transferable skills. Finally, the analysis reveals important policy implications. Because changes to unemployment benefits affect sectors differently, these changes impact the economy's sectoral composition and aggregate productivity.
Keywords: E2; J6; J08; J21; J24; Q43; 330; Sectoral Labour Reallocation; Adjustment Costs; Search and Matching; Skills and Training; Unemployment; Strukturelle Arbeitslosigkeit; Suchtheorie; Anpassungskosten; Qualifikation; Arbeitslosenversicherung; Kanada